Check sibling questions


Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Ex 12.2, 1 Factorise the following expressions. (vii) 〖"(l + m)" 〗^2 – 4lm (Hint: Expand 〖"(l + m)" 〗^2 first)〖"(l + m)" 〗^2 – 4lm = 𝑙^2+𝑚^2+2𝑙𝑚 −4𝑙𝑚 = 𝑙^2+𝑚^2+𝑙𝑚 (2−4) = 𝒍^𝟐+𝒎^𝟐−𝟐𝒍𝒎 = (𝒍−𝒎)^𝟐 Using (𝒂+𝒃)^𝟐=𝑎^2+𝑏^2+2𝑎𝑏 Here, 𝑎 = l and b = m Using (𝒂−𝒃)^𝟐=𝑎^2+𝑏^2−2𝑎𝑏 Here, 𝑎 = l and b = m

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.